A spy in the house of love - Nin, Anaïs 1903-1977 (Penguin Books, 2012)
Beautiful, bored and bourgeoise, Sabina leads a double life inspired by her relentless desire for brief encounters with near-strangers. Fired into faithlessness by a desperate longing for sexual fulfilment, she weaves a sensual web of deceit across New York. But when the secrecy of her affairs becomes too much to bear, Sabina makes a late night phone-call to a stranger from a bar, and begins a confession that captivates the unknown man and soon inspires him to seek her out
Originally published: New York: British Book Centre, 1954; London: Peter Owen, 1971
Keywords: Women / Sexual behavior / Fiction; Erotic stories; Frau